Ensino-aprendizagem da dança para formação de cidadãos críticos e participativos - PINTO, Andressa Chagas (2019)
The present study aims to investigate the relationship of students with dance in the teaching-learning process and the perception about the importance of this content for the formation of critical and participative citizens. The sample consisted of 69 high school students, aged 14 to 18 years old, enrolled in a state school in the city of Belém do Pará. As a data collection instrument, a questionnaire was used with five questions (open and closed) about their relationship with dance. The results showed that 55.07% practice in school and 44.93% say they do not practice in this space. While out of school 34.78% say they practice and 65.22% say they do not practice. When asked if the students feel they lack of practicing dance in physical education classes, 44.93% said they miss and 55.07% do not miss. Regarding the student's understanding of the importance of this content for their training, 46.38% answered that yes and 53.62% did not. Regarding the students' understanding of the influence of the experience of this content in their social relations, 33.78% did not influence, 44.92% answered that influence, and of which, 11.59% attributed influence to the expression of feelings , 5.08% the influence in the culture and 4.63% to work in group. In the light of the results, we conclude that dance can influence student relations as well as dance / world readers, as they can express themselves and become critical and participative citizens.